Recognising value tensions that underlie problems in inclusive education - Norwich, Brahm (Cambridge Journal of Education, 2014)
This paper aims to examine some tensions that underlie inclusive education as regards pupils with disabilities and difficulties. Two key tensions are analysed: difference as enabling–stigmatising (dilemmas of difference) and participation–protection, both of which can lead to significant dilemmas. Berlin’s hedgehog–fox distinction about the unity (hedgehog view) or plurality (fox view) of values is adopted and extended to different positions about inclusion. More radical versions of inclusion are portrayed as expressing rigid hedgehog positions that commit to one big value and so ignore other important values. However, in veering to a fox perspective, the argument recognises the need for tensions to be resolved. This resolving tendency expresses an integrating aim that seeks a unified perspective, even if it is not a final and absolute one. In this way some balance between a unitary view (hedgehog view) and a plurality view (fox view) can be achieved.
Publisher: Routledge _eprint: https://doi.org/10.1080/0305764X.2014.963027